The monoid of endomorphisms of disconnected hypergraphs - Zhuchok, Yu.V. (Algebra and Discrete Mathematics, 2013)
We prove that the monoid of endomorphisms of an arbitrary disconnected hypergraph is isomorphic to a wreath product of a transformation semigroup with a certain small category. For disconnected hypergraphs we also study the structure of the monoid of strong endomorphisms and the group of automorphisms.